Comparison of Interpolation Techniques for enlarging image with LL Sub-band of IWT transform - Patel, Hiral (International Journal of Computer Sciences and Engineering, 2023)
Digital images are an important part of the digital world. Majority of transactions are handled through digital images in place of physical image. Electronic security is also the concerned task for digital images. Data hiding techniques are available through which security can be provided to the images. Digital Image Tampering is one of the issues where the actual content of the original image is lost. To hide the data, Integer Wavelet Transform places an important role which can help in hiding data without loss of content. But during tampering the image content may loss the data which can affect the sub-bands which are generated through IWT transform. If during self-recovery stage, if the LL sub-band is retrieved properly then using Interpolation technique, the image can be enlarged. This paper demonstrates the comparison of Interpolation techniques with respect to LL sub-band of IWT transform. As outcome, it is found that Lancoz3 Interpolation technique is better to use as compare to Nearest Neighbor, Bilinear, Bicubic, Lancoz2 interpolation techniques. The outcomes are measured using PSNR, Sum of Absolute Difference and Average of Absolute Difference.